Phytoplankton community diversity is influenced by environmental factors in the coastal East China Sea. Issue 1 (2nd January 2016) - Xu, Zhifang; Chen, Ying; Meng, Xi; Wang, Fujiang; Zheng, Zhijian
Abstract : Surface seawater was collected in four different seasons in the coastal East China Sea adjacent to the Yangtze River Estuary and phytoplankton community diversity was analysed using rbc L genetic markers. Phytoplankton diversity (Shannon Index) was found to be highest in autumn and lowest in summer, which was mainly controlled by seawater temperature, river runoff, the Taiwan Warm Current and possibly other environmental factors. For taxa characterized by Form IAB rbc L, the abundance of Chlorophyta was much greater than those of Proteobacteria and Cyanobacteria throughout the year with the most dominant taxa being Bathycoccus prasinos (Chlorophyta) in spring and Micromonas sp. (Chlorophyta) in other seasons. For taxa identified by Form ID rbc L, Coscinodiscophyceae (diatoms) constituted the largest group (most clones) in the phylogenetic tree. Dinophysis fortii (a dinoflagellate) was found to be the most abundant species in winter and spring and Skeletonema spp. (a diatom) dominated the phytoplankton community in summer and autumn. The seasonal dominance of Dinophysis fortii agreed well with the recently increasing proportion of dinoflagellates in the phytoplankton community in the coastal East China Sea. The abundance of Dinophysis fortii was negatively correlated with seawater temperature, suggesting that harmful algal blooms caused by this species may primarily occur in spring.